Henry hikes to Fitchburg - Johnson, D. B. frey50 (Boston : Houghton Mifflin, 2000)
While his friend works hard to earn the train fare to Fitchburg, young Henry Thoreau walks the thirty miles through woods and fields, enjoying nature and the time to think great thoughts. Includes biographical information about Thoreau.
Picture book.
Keywords: Thoreau, Henry David, -- 1817-1862; Thoreau, Henry David, -- 1817-1862; Nature; Walking -- Fiction